Development of Moodle-Assisted Short Story Writing Teaching Materials in Differentiated Learning at Triguna High School 1956 - Andayani, Sri; Murtadho, Fathiaty; Utami, Sintowati Rini (Electronic Journal of Education, Social Economics and Technology, 2026)
This research aims to develop teaching materials for writing short stories with the help of Moodle with a differentiated learning approach at SMA Triguna 1956 to overcome student demotivation and the limitations of conventional methods. Using the Research and Development (RD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, this research involves needs analysis, expert validation (media and materials), and trials to grade XI students. The validation results showed a very high level of eligibility, namely 91.07% (media experts) and 88.3% (material experts), while the students' trial obtained an average score of above 74%, proving that this teaching material is effective and suitable for use. The research findings revealed that the integration of Moodle with a differentiation approach successfully facilitated more adaptive learning, although further testing in various school contexts was required, technology training for students, and the development of materials for other language skills. This study makes a significant contribution to the development of differentiation-based digital teaching materials, with recommendations for further research to evaluate its long-term impact.